2016
DOI: 10.3945/jn.116.234575
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to the Chinese Famine in Childhood Increases Type 2 Diabetes Risk in Adults

Abstract: Exposure to the Chinese famine in childhood was related to an increased risk of adulthood T2D and hyperglycemia, particularly in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
78
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 33 publications
13
78
2
Order By: Relevance
“…Similar findings have been demonstrated in previous studies of large populations subject to prolonged periods of famine and distress during times of war . Holocaust survivors with posttraumatic stress disorder (PTSD) had higher rates of myocardial infarction, chronic diseases, and cancer than individuals with PTSD from other traumatic events .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similar findings have been demonstrated in previous studies of large populations subject to prolonged periods of famine and distress during times of war . Holocaust survivors with posttraumatic stress disorder (PTSD) had higher rates of myocardial infarction, chronic diseases, and cancer than individuals with PTSD from other traumatic events .…”
Section: Discussionsupporting
confidence: 82%
“…Other studies assessing morbidity in Dutch famine survivors found higher body mass index and higher cardiovascular mortality in exposed women but not men. Similar sex‐related findings were found in famine studies conducted in Biafra, China, and Austria …”
mentioning
confidence: 99%
“…Animal studies have reported that prolonged postnatal malnutrition impairs β‐cell development . Some studies on the Great Chinese Famine also showed that famine in childhood was related to an increased risk of adulthood T2DM and hyperglycemia …”
Section: Discussionmentioning
confidence: 70%
“…Several studies on the association between the Great Chinese Famine and the risk of T2DM or metabolic syndrome have been published . Unfortunately, few studies were conducted nationwide.…”
Section: Introductionmentioning
confidence: 99%
“…A significant interaction between the level of famine severity in the areas of exposure throughout the prenatal and childhood periods and the risk of T2D in adulthood has been observed. In another Chinese population, 1.44-fold higher risk of T2D development in the middle-childhood-exposed group, and 1.5-fold higher risks of hyperglycaemia in both the middle- and late-childhood-exposed groups were demonstrated compared to the unexposed group [72]. Remarkably, those individuals who experienced more severe famine in childhood had a 38% higher risk of T2D development than those exposed to less severe famine.…”
Section: Quasi-experimental Design In Studying the Developmental Omentioning
confidence: 99%